2015
DOI: 10.1016/j.ntt.2015.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Developmental origin of abnormal dendritic growth in the mouse brain induced by in utero disruption of aryl hydrocarbon receptor signaling

Abstract: Increased prevalence of mental disorders cannot be solely attributed to genetic factors and is considered at least partly attributable to chemical exposure. Among various environmental chemicals, in utero and lactational dioxin exposure has been extensively studied and is known to induce higher brain function abnormalities in both humans and laboratory animals. However, how the perinatal dioxin exposure affects neuromorphological alterations has remained largely unknown. Therefore, in this study, we initially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 51 publications
4
41
0
Order By: Relevance
“…This observation is in agreement with our previous study (Kimura et al, 2015) that demonstrated abnormal dendritic morphology in the CA-AhRtransfected pyramidal neurons of the hippocampus in the developing mice from the same littermates as used in the present study. Thus, it is likely that disruption of neuronal migration induces abnormal dendritic morphology in the developing hippocampus.…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…This observation is in agreement with our previous study (Kimura et al, 2015) that demonstrated abnormal dendritic morphology in the CA-AhRtransfected pyramidal neurons of the hippocampus in the developing mice from the same littermates as used in the present study. Thus, it is likely that disruption of neuronal migration induces abnormal dendritic morphology in the developing hippocampus.…”
Section: Discussionsupporting
confidence: 94%
“…AhR deletion mutant that lacks part of the ligand-binding domain functions as a CA-AhR that induces Cyp1a1 expression (Kimura et al, 2015). This CA-AhR cDNA fragment was amplified by PCR using the specific primers 5′-CTCGAGGCGGGCACCATGAGCAGCGGCGCCA -3′ and 5′-CTCGAGTCAACTCTGCACCTTGCT-3′ and pQCXIN-CA-AhR-EGFP (a kind gift from Dr. Yoshiaki Fujii-Kuriyama, then at the University of Tsukuba and Dr. Tomohiro Ito at the National Institute for Environmental Studies) as a template.…”
Section: Vector Constructionmentioning
confidence: 99%
See 3 more Smart Citations